Monomer Release from Nanofilled and Microhybrid Dental Composites after Bleaching - Tabatabaee, Masumeh Hasani (Tehran University of Medical Sciences, 2014)
OBJECTIVE: The aim of this study was to assess the effect of bleaching on elution of monomers from nanofilled and microhybrid composites. MATERIALS AND METHODS: 80 samples (5mm diameter and 3mm thickness) of each composite were prepared. After curing, half of them were randomly polished. Each group was divided into 8 subgroups and immersed in water or 10%, 20% and 30% H2O2 for 3 or 8 hours. Eluted Bis-GMA (Bis-phenol A Glycidyl Dimethacrylate), TEGDMA (Triethyleneglycol Dimethacrylate), UDMA (Urethane Dimethacrylate) and BisEMA (Bis-phenol A ethoxylate Dimethacrylate) were quantified by high performance liquid chromatography and the results were analyzed by univariate ANOVA and t-test (P<0.05). RESULTS: Bleach significantly increased the overall release of monomers (P<0.001); TEGDMA was released more than Bis-GMA (P<0.001). Supreme released more TEGDMA compared to Z250 (P<0.001). Bleaching increased the release of this monomer (P<0.001). Increasing both the concentration of H2O2, and the immersion time, increased the release of TEGDMA (P<0.001). Polishing had no effect on release of this monomer (P=0.952). Supreme released more Bis-GMA than Z250 (P=0.000). The more concentrated H2O2 caused more elution of Bis-GMA (P= 0.003); while the effect of immersion time was not significant (P=0.824). Polishing increased the release of Bis-GMA (P=0.001). Neither the type of composite nor Bleaching had any effect on release of UDMA (P=0.972) and (P=0.811) respectively. Immersion duration increased the release of UDMA (P=0.002), as well as polishing (P=0.024). CONCLUSION: Bleaching increased the release of monomers. Nanofilled composites released more monomer than the microfilled.